2020
DOI: 10.36835/iqtishoduna.v9i2.489
|View full text |Cite
|
Sign up to set email alerts
|

Stock Selectivity Skill, Market Timing Ability, Risiko, Size, and Comparison of Performance Islamic Share Mutual Funds

Abstract: Indonesia is one of the countries with the largest Muslim population about 87%. The high population of the Muslim in Indonesia should be able to provide great potential in terms of Islamic finance as investment activity, which will certainly contribute positively to the Indonesian economy. Investors will always be interested in investment with high return and low risk. One of the alternative is mutual fund especially sharia equity mutual funds. The choice of the right mutual fund should pay attention to how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This ability is an important aspect of investment management skills, especially for fund managers or investors who manage stock portfolios. Stock selection skill is the ability to forecast or predict those assets that may produce abnormal profits or profits that are superior to those expected in the future (Lailiyah & Setiawan, 2020). Enhanced proficiency in selecting stocks by investment managers will contribute to the growth in returns for the Islamic stock mutual funds under their management.…”
Section: Figure 2 Development Of Nav Of Sharia Equity Mutual Fund Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability is an important aspect of investment management skills, especially for fund managers or investors who manage stock portfolios. Stock selection skill is the ability to forecast or predict those assets that may produce abnormal profits or profits that are superior to those expected in the future (Lailiyah & Setiawan, 2020). Enhanced proficiency in selecting stocks by investment managers will contribute to the growth in returns for the Islamic stock mutual funds under their management.…”
Section: Figure 2 Development Of Nav Of Sharia Equity Mutual Fund Unitmentioning
confidence: 99%
“…However, market timing ability does not affect the performance of Sharia equity mutual funds in Indonesia. Another study conducted by Lailiyah & Setiawan (2020) asserts that mutual fund size, stock selection skill, and market timing ability do affect the performance of Sharia equity mutual funds.…”
Section: Figure 2 Development Of Nav Of Sharia Equity Mutual Fund Unitmentioning
confidence: 99%
“…Bayu et al (2018) previously discovered that the size of mutual funds positively affects the performance of equity funds when using the efficient market theory approach. It has been shown that the bigger the fund managed by the investment manager, the better the performance of the mutual fund through optimal returns gained in the future, as shown by studies by Grace (2019) and Lailiyah and Setiawan (2020). Before this, it had been established by Busse et al (2013) that significant mutual funds greatly impact mutual fund performance compared to small mutual funds.…”
Section: Mutual Fund Size and The Performance Of Mutual Fundmentioning
confidence: 99%
“…Since they continuously look for undervalued stocks and rebalance their portfolios' beta depending on the various market factors such as volatility, liquidity, and returns. Despite numerous studies on SCF manager's skills, these studies generally focus on the ability to select stocks and forecast market returns (Alsharif & Ahmad, 2021; Boo et al, 2017; Lailiyah & Setiawan, 2020; Mansor et al, 2015; Mansor et al, 2020; Mansor & Bhatti, 2011; Mirza et al, 2022; Mohammad & Ashraf, 2015; Setiawan & Wati, 2019; Zouaoui, 2019). Fewer studies simultaneously investigate the other dimensions of SCF manager skill: liquidity, volatility, stock selectivity, high order co‐moments, and return timing.…”
Section: Introductionmentioning
confidence: 99%
“…Second, most existing studies use unconditional (static) regression models to estimate SCF fund managers' selection and timing abilities based on standardized periods (Alsharif & Ahmad, 2021; Boo et al, 2017; Lailiyah & Setiawan, 2020; Mansor et al, 2020; Mirza et al, 2022; Setiawan & Wati, 2019; Zouaoui, 2019). A time‐invariant skill level is implicitly assumed in the existing studies' unconditional model of SCF managers.…”
Section: Introductionmentioning
confidence: 99%